Recruitment, selection, training practices and employee performance in service sector institutions of Nepal - Pradhan, Gopal Man (Journal of Nepalese Management Academia, 2023)
This research is based on the analysis of relationship of recruitment, selection, and training with that of employee performance in service sector institutions of Nepal. The elements recruitment process, selection process, and employee training are considered as independent variables whereas employee performance is taken as dependent variable. This study is based on analysis of information gained through service sector institutions of Nepal consisting of hospitals, telecommunications, and airlines. In this research work, in total 321 questionnaires were distributed and 244 respondents provided their response, which was the basis of study. The statistical tools such as descriptive statistics, correlation, and regression analysis have used to study the data collected through questionnaire. In this study it is found that recruitment, selection, and training have significant position relation with employee performance. But, when examining the beta coefficient, it was explored that compassion to training is higher followed by selection process on employee performance. The conclusion is that if Nepalese service sectors define and implement specific procedures of recruitment, selection, and training process, it can improve the level of employee performance. The improvement of employee performance would be supportive for improvement of overall organizational performance.